"Category 4A" microcalcifications: how should this subcategory be applied to microcalcifications seen on mammography?. (February 2018) - Kim, Jihee; Kim, Eun-Kyung; Kim, Min Jung; Moon, Hee Jung; Yoon, Jung Hyun
Background: The BI-RADS provides descriptors for microcalcifications based on morphology and distribution. However, the descriptor for category 4A microcalcifications is not specified in the 5th BI-RADS nor in the prior editions. Purpose: To investigate how the category 4A assessment is applied to suspicious microcalcifications, and the appropriate descriptors for category 4A assessment for microcalcifications seen on mammography. Material and Methods: From June 2008 to November 2011, 296 women with 305 suspicious microcalcifications that were assessed as BI-RADS category 4A, who underwent imaging-guided biopsy or surgery, were included. Mammograms were reviewed and imaging features were analyzed according to the morphology and distribution descriptors of the 5th edition of BI-RADS. Pathological results were considered as the reference standard. Positive predictive values were calculated and compared between morphology and distribution descriptors. Results: The overall positive predictive value (PPV) of category 4A microcalcifications was 17.7% (54/305). Most common descriptors for category 4A microcalcifications were amorphous morphology (73.1%) and grouped distribution (71.1%). PPVs of individual morphology descriptors were as follows: amorphous = 7.2%; coarse heterogeneous = 12.8%; fine pleomorphic or fine linear/fine linear branching = 91.4% ( P  < 0.001). PPVs of distribution descriptors were as follows: regional = 13.2%; grouped = 16.1%; linear/segmental = 54.5% ( P  < 0.001). For morphology and distribution descriptors combinations, PPVs for amorphous/regional and amorphous/grouped microcalcifications were 6.8% and 6.9%, while PPVs of other combinations were higher than 10%, respectively. Conclusion: Common descriptors used in category 4A assessment for microcalcifications are amorphous morphology and grouped distribution. PPV of amorphous/regional and amorphous/grouped microcalcifications were suitable for category 4A assessment.